ANALYSIS OF THE APPLICATION OF ACCOUNTING BASED ON SAK EMKM TO UMKM FEBRI STORES IN SIMPANG EMPAT DISTRICT - Nurlela; Muharsyah Hafiz; Ita Purnamasri Br Sitepu (SEAN Institute, 2022)
Febri stores is an UMKM owned by Mr. Suratman Sembiring has his address in Kec. Intersection 4 Kab. Karo, this UMKM, is engaged in the basic food trade sector. This business has been established for more than 8 years, but Mr. Suratman has not made financial reports in accordance with SAK EMKM rules. This study aims to assist the application of accounting, namely making financial reports based on SAK EMKM using the Excel For Accounting application. The type of data used in this research is primary data, the data source used is internal data. Data collection techniques used were observation interviews, interviews and documentation, while the data analysis method used was a quantitative descriptive method. Based on the results of the study, it was found that the total profit of UMKM Toko Febri when SAK EMKM was applied was more accurate because all assets, capital, and financial transactions were recorded chronologically and systematically. The resulting financial reports can describe the business conditions of the Febri Toko UMKM in detail. This condition is also facilitated by the use of the Excel For Accounting application so that it can complete the accounting cycle to financial reports accurately.